2022
DOI: 10.3390/ijerph191710620
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors That Suppress Help-Seeking among Middle-Aged and Older Adults Living Alone

Abstract: Help-seeking among destitute adults has not been adequately investigated. Therefore, this study clarifies the mechanisms that suppress help-seeking in middle-aged and older adults living alone. Data were collected from 1274 individuals (aged 50–79 years) who were living alone, using a survey that measured future time perspective, barriers to help-seeking, help-seeking intentions, and current and childhood economic statuses. Men living alone experienced lower help-seeking intention than women, were more likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…Mackenzie et al found that women generally have more positive mental health help-seeking attitudes (23), which could be due to cultural norms that portray men as strong and unsupportive, preventing them from expressing their struggles and failures (24). Additionally, research suggests that women tend to have stronger social relationships than men (25). Therefore, when developing mental health help-seeking attitudes promotion programs in the western region of Iran, it is essential to consider both genders.…”
Section: Discussionmentioning
confidence: 99%
“…Mackenzie et al found that women generally have more positive mental health help-seeking attitudes (23), which could be due to cultural norms that portray men as strong and unsupportive, preventing them from expressing their struggles and failures (24). Additionally, research suggests that women tend to have stronger social relationships than men (25). Therefore, when developing mental health help-seeking attitudes promotion programs in the western region of Iran, it is essential to consider both genders.…”
Section: Discussionmentioning
confidence: 99%